Mining user generated content - Moens, Marie-Francine, 1957-; Li, Juanzi; Chua, T. S. (Tat-Seng), 1955- (Chapman & Hall/CRC social media and social computing series., 2014)
Originating from Facebook, LinkedIn, Twitter, Instagram, YouTube, and many other networking sites, the social media shared by users and the associated metadata are collectively known as user generated content (UGC). To analyze UGC and glean insight about user behavior, robust techniques are needed to tackle the huge amount of real-time, multimedia, and multilingual data. Researchers must also know how to assess the social aspects of UGC, such as user relations and influential users. Mining User Generated Content is the first focused effort to compile state-of-the-art.